Transient and sustained afterdepolarizations in accessory olfactory bulb mitral cells are mediated by distinct mechanisms that are differentially regulated by neuromodulators - Shpak, Guy; Zylbertal, Asaph; Wagner, Shlomo (Frontiers in Cellular Neuroscience, 2015)
Social interactions between mammalian conspecifics rely heavily on molecular communication via the main and accessory olfactory systems. These two chemosensory systems show high similarity in the organization of information flow along their early stages: social chemical cues are detected by the sensory neurons of the main olfactory epithelium and the vomeronasal organ. These neurons then convey sensory information to the main (MOB) and accessory (AOB) olfactory bulbs, respectively, where they synapse upon mitral cells that project to higher brain areas. Yet, the functional difference between these two chemosensory systems remains unclear. We have previously shown that MOB and AOB mitral cells exhibit very distinct intrinsic biophysical properties leading to different types of information processing. Specifically, we found that unlike MOB mitral cells, AOB neurons display persistent firing responses to strong stimuli. These prolonged responses are mediated by long-lasting calcium-activated non-selective cationic current (Ican). In the current study we further examined the firing characteristics of these cells and their modulation by several neuromodulators. We found that AOB mitral cells display transient depolarizing afterpotentials (DAPs) following moderate firing. These DAPs are not found in MOB mitral cells that show instead robust hyperpolarizing afterpotentials. Unlike Ican, the DAPs of AOB mitral cells are activated by low levels of intracellular calcium and are relatively insensitive to flufenamic acid. Moreover, the cholinergic agonist carbachol exerts opposite effects on the persistent firing and DAPs of AOB mitral cells. We conclude that these phenomena are mediated by distinct biophysical mechanisms that may serve to mediate different types of information processing in the AOB at distinct brain states.